THE THREE CERTAINTIES REQUIRED TO DECLARE A TRUST – OR IS IT FOUR? "DISTRIBUTIONAL CERTAINTY". (July 2020) - Wilde, David
Abstract: This article argues certainty in trusts is better understood by recognising a fourth certainty: "distributional certainty". Distributional certainty is required in private trusts that involve dividing the property between beneficiaries: their shares must be clear. Distributional uncertainty is not, as usually understood, merely an instance of uncertainty of property: it has differing consequences, special resolution techniques, and may explain "administrative unworkability" in discretionary trusts. Distributional certainty is not required in charitable trusts. But this is not, as usually understood, merely an instance of the rule that charitable trusts do not need certainty of objects: it is an independent proposition.